Original paperTHE EFFECT OF RESISTANCE AND ENDURANCE EXERCISE TRAINING ON MUSCLE PROTEOME EXPRESSION IN HUMAN SKELETAL MUSCLE - Son, H.J.; Kim, H.J.; Kim, C.K. (Biology of Sport, 2012)
To investigate the effect of resistance and endurance training on muscle proteome expression, samples of vastus lateralis from 10 physically active young men were analysed by 2-dimensional electrophoresis (2-DE) and matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Differential patterns of protein expression were determined after 4 weeks of endurance or resistance exercise training. Following endurance exercise training, carbonic anhydrase III immunoglobulin heavy chain, myosin heavy chain 1, titin, chromosome 12, and fructose-1,6-bisphosphatase 2 were up-regulated while pyruvate kinase 3 isoform, ubiquitin carboxyl-terminal hydrolase, and phosphoglucomutase were down-regulated. After the 4 weeks of resistance exercise training, five proteins, apolipoprotein A-IV precursor, microtubule-actin cross linking factor 1, myosin light chain, growth hormone inducible transmembrane protein, and an unknown protein were up-regulated and pyruvate kinase 3 isoform, human albumin, and enolase 3 were down-regulated. We conclude that endurance and resistance exercise training differently alter the expression of individual muscle proteins, and that the response of muscle protein expression may be associated with specific myofibre adaptations to exercise training. Proteomic studies represent one of the developing techniques of metabolism which may substantially contribute to new insights into muscle and exercise physiology.